2022
DOI: 10.3389/fendo.2022.1030216
|View full text |Cite
|
Sign up to set email alerts
|

Early-life weight gain patterns of term small-for-gestational-age infants and the predictive ability for later childhood overweight/obesity: A prospective cohort study

Abstract: ObjectivesWe aimed to identify the weight gain patterns of small-for-gestational age (SGA) infants in early life and to explore the predictive value for later overweight/obesity in childhood.MethodsWe obtained data from a prospective cohort including term SGA infants born between January 2006 and November 2015 who received regular health care from birth to 5 years in West China Second University Hospital, Chengdu, China. A latent class growth analysis (LCGA) was applied to group children with similar growth tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This interesting finding highlights the potential complex interplay between possible early catch-up growth among those born SGA, lifestyle factors later in life, and the nutritional challenges prevalent in remote communities ( 29 , 43 ). Rapid catch-up growth among SGA infants is a risk factor for being overweight/obese at 2–5 years of age ( 9 ) and is associated with increased fat mass at 9 years of age ( 37 ), and fat mass with central adiposity at 32 years of age ( 44 ). Lower birth weight combined with faster growth in the first 5 years has also been associated with increased hepatic fat in early childhood ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…This interesting finding highlights the potential complex interplay between possible early catch-up growth among those born SGA, lifestyle factors later in life, and the nutritional challenges prevalent in remote communities ( 29 , 43 ). Rapid catch-up growth among SGA infants is a risk factor for being overweight/obese at 2–5 years of age ( 9 ) and is associated with increased fat mass at 9 years of age ( 37 ), and fat mass with central adiposity at 32 years of age ( 44 ). Lower birth weight combined with faster growth in the first 5 years has also been associated with increased hepatic fat in early childhood ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al, found dynamic BMI growth patterns (such as BMI catch-up and stable overweight) were more predictive, and thus more informative, than static BMI measurements of cardiovascular structure and function in early childhood (32). Rapid weight gain in early childhood (or catch-up growth) has been associated with an increased risk of overweight, obesity and other chronic diseases during later childhood and adulthood (33)(34)(35)(36). Additionally, catch-up growth has been associated with various factors such as altered insulin metabolism (37,38) and hence an increased risk of Type II diabetes (39), increased systolic blood pressure (40), increased risk of coronary heart disease (7) and an increased risk of childhood asthma (41) Various factors may modify the risk of rapid weight gain or obesity, including bottle feeding, shorter gestation age and being firstborn (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…32 There is growing evidence that children who grow up quickly during childhood are more likely to be obese and have metabolic disorders such as insulin resistance and non-insulin-dependent diabetes, hypertension and cardiovascular disease during adulthood. 33 Li et al 34 found that the extremely rapid weight gain pattern of term SGA infants from birth to 2 years was significantly related to the increased risk of overweight/obesity at 2-5 years in later life. The risk was approximately two times higher than that of full-term non-SGA infants.…”
Section: Open Accessmentioning
confidence: 99%